Gabon : Staff Report for the 2005 Article IV Consultation, Third Review Under the Stand-By Arrangement, and Review of Financing Assurances. (IMF Staff Country Reports; Country Report ;, 2005)
The staff report for the combined consultation and 2005 Article IV Consultation on Gabon highlights economic developments and policies. Preparing Gabon for the post-oil era requires strengthening the efficiency of the public sector and providing a framework for private sector development to raise the productivity of the Gabonese economy. In the public sector, improving expenditure management, especially of public investment, is essential. Gabon remains keen to seek a multiyear follow-up program after the expiration of the Stand-By Arrangement.